Christianity in Africa: A Beacon of Hope for Christianity in Europe - Michael Fuseini Wandusim (Centre for Behaviour and Wellness Advocacy, 2015)
World Christianity has experienced several changes including its spread and decline across the world. Following what Andrew F. Walls terms as "Serial character of Christian advance," Christianity has moved from Europe, its previous heartland to other continents like Africa, Asia and Latin America. Today in Europe, in general terms, Christianity can be described in words such as 'declining', 'empty pews', 'dying', 'few pews filled with only old folks', etc. Given the seemingly hopeless nature of the condition of Christianity in Europe, this article seeks to argue that Christianity in Africa provides hope for world Christianity in the light of the dying state of it in Europe, its erstwhile heartland. The article explores the phenomena of globalization and migration as media through which Christianity in Africa provides this hope to Europe and World Christianity at large.